Conceptualising Elder Abuse: Does this Label Fit? - Clare, M.; Clare, B.; Blundell, Barbara; Clare, J. (Australian College for Child and Family Protection Practitioners Inc., 2014)
This article is based on the findings of two recent West Australian studies (Black Blundell & Clare, 2012; Clare, Black Blundell & Clare, 2011), which, respectively consider: the nature and extent of elder abuse in the Western Australian community; and elder abuse services for older Australians whose first language is not English. The focus of the paper is twofold: it considers the conceptual difficulties associated with identifying who should be included under the umbrella term ‘elderly’, and the equally problematic definition of behaviours deemed to be abusive. It goes on to reflect on the challenges associated with the provision of services for older people subject to abuse. The paper reports the recommendations that emerged from the WA studies. It identifies the need for an integrated service response that explicitly acknowledges the continuum of needs and concerns of older Australians and is clearly located within a broad-based legislative, policy and practice framework.